1660 İstanbul yangınının sosyo-ekonomik tahlili - Yıldız, Kenan (My University, 2013)
Ahşap mimarisiyle tanınmış ve şehir kimliğini oluşturmuş olan İstanbul (sur içi), Osmanlı dönemi boyunca her yüzyılda meydana gelmiş olan küçüklü büyüklü yangınlardan dolayı harap olmuş ve yeniden inşa edilmiştir. Fakat, her ne kadar halkı ve devleti yıllarca maddi zorluklara sokmuş olan bu arızi afet dolayısıyla kârgir yapıya geçme teşebbüslerinde bulunulduysa da, gerek taş malzemenin temin edilmesinin maddi zorlukları, gerekse bu bölgede deprem riskinin büyük olması gibi sebeplerle bu mümkün olmamıştır. Neticede, özellikle mesken ve dükkân mimarisinde XIX. yüzyıla kadar ahşabın hakim konumunda önemli bir değişiklik olmamıştır. Bu da, zaten söndürme tekniklerinin yeterli olmadığı bu çağlarda meydana gelen herhangi bir yangında şehrin önemli ölçüde zarar görmesi sonucunu doğurmuştur. Yirmiden fazla yangının meydana geldiği XVII. yüzyılda İstanbul’da görülen ve etkileri bakımından diğerlerinden ayrılan iki büyük yangın (1633 ve 1660 yıllarında) vakıf kurumlarına da büyük zararlar vermiştir. Ortaya çıkan olağan üstü şartlar gereği bu kurumların, yerlerini yeniden inşa ettirmeleri, özellikle maddi imkansızlıklar sebebiyle önemli bir sorun olarak idarecileri meşgul etmiştir. Yangın sonrasıda ortaya çıkan arsaların bir kısmı el değiştirirken, bir kısmının önceden sahip olduğu resmi ve hukuki durumu farklılaşmış ve bazıları da muhtelif sebeplerle imar edilemeden onlarca yıl âtıl kalmıştır. Yapılacak binanın ev veya dükkân olması, maddi getirisi, konumu gibi sebepler, yangın mahallerinin ve arsaların yeni hukuki durumlarının şekillenmesinde birinci derecede etken olmuştur.

Istanbul (intra-muros), which is well-known with its wooden architecture and created its own city-identity, had been devastated by big and small scales fires that occurred in every century throughout the Ottoman Empire and then reconstructed. Although it was attempted to transform wooden architecture, which cost financial difficulties to both people and the state, to masonry, it had not happened an important change in residential and commercial architecture until 19th century due to both the financial difficulties to supply stone materials and the high risks in the region. This was also resulted in damaging significant parts of city in any fire occurred in those centuries because of insufficient extinguishing equipments and techniques. In 17th century, more than twenty fires were occurred in Istanbul, and among them two fires, which took place in 1633 and 1660 respectively, differed from the rest of them in terms of consequences and big damages they gave to the properties of the foundations. Due to the lack of sources and financial deficiencies, to reconstruct and replace these damaged properties took relatively long time and kept the officials busy. Aftermath of these fires, some of properties and lands were changed hands, some their official and legal statuses were altered from their previous position, and some of them remained inert for various reasons over years. Particularly, in the 1660 fire which is accepted as the greatest one that took place in Istanbul burned down two third of the city and underwent change in the peninsula in terms of both its population and skyline. Meanwhile, fires also caused significant changes in the settlement and population of city. The construction of New Mosque is a good example for that and it engendered social and political changes in Eminönü area. The construction of mosque was initiated by Safiye Sultan in 1597 and upon her death it was interrupted for a long time due to high costs. Aftermath of given fire, Hatice Turhan Sultan ordered to restart the construction of the mosque, and this case was one of fundamental causes for a change. To this end, with Hatice Turhan Sultan, Muslim foundations were swapped with non-Muslims’ properties and lands. In addition to that, to meet the requirement of mosque congregation, the tenants of foundations which were largely Jews moved to Hasköy and Balat, and consequently Muslims were settled down in area where Jews left. This practice showed an important population policy in that era.
Keywords: Sosyo-Ekonomik Durum_İstanbul (Türkiye); Tarih; Yakınçağ